2017
DOI: 10.1371/journal.pmed.1002218
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Hospital-Based Surveillance for Outbreak Detection in Bangladesh: Analysis of Healthcare Utilization Data

Abstract: BackgroundThe International Health Regulations outline core requirements to ensure the detection of public health threats of international concern. Assessing the capacity of surveillance systems to detect these threats is crucial for evaluating a country’s ability to meet these requirements.Methods and FindingsWe propose a framework to evaluate the sensitivity and representativeness of hospital-based surveillance and apply it to severe neurological infectious diseases and fatal respiratory infectious diseases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 29 publications
1
38
0
Order By: Relevance
“…20 Our findings are consistent with another study in Bangladesh that distance from health care facility is a major barrier for seeking care, even for severe illnesses. 21 These findings suggested that basic improvement in transportation infrastructure could reduce child mortality in rural Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…20 Our findings are consistent with another study in Bangladesh that distance from health care facility is a major barrier for seeking care, even for severe illnesses. 21 These findings suggested that basic improvement in transportation infrastructure could reduce child mortality in rural Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulties of poor populations reaching hospitals include limited geographical accessibility as well as substantial financial barriers [30]. Models using healthcare utilization data collected from the catchment areas of the same surveillance hospitals in Bangladesh presented here showed that case detection probabilities decrease steeply as distance from the hospital site increases [31] and that hospital-based surveillance misses nearly half of all Nipah outbreaks [32]. Finally, the selection of hospitals as surveillance sites and the requirement that patients be admitted to meet the case definition likely biases our system to detect more severe disease, as patients with more mild illnesses either do not come to hospitals or do not require admission.…”
Section: (A) Selection Of Surveillance Sitesmentioning
confidence: 73%
“…Direct community involvement in the detection and reporting of potentially important public health events can overcome many limitations of routine indicator-based surveillance in detecting outbreaks while they are small and localized. [13][14][15][16][17] In the past, most community-based surveillance programs have focused on reporting single diseases, such as a specific vaccine-preventable disease, or one targeted for elimination (eg, guinea worm). 4,5,13,18 The current community event-based surveillance study took a broad approach, targeting the pathogens of highest concern to the ministry of health, and included signals that may detect emerging and reemerging threats as part of the development of an early warning and response system.…”
Section: Discussionmentioning
confidence: 99%